Education for a Faith in the Future - Das, Manoj (JOURNAL OF INDIAN EDUCATION, 2008)
In the history of recorded time there had never been another century more dominated by paradox than the 20th century – the formidable backdrop of the current decade. Great adventures and explorations were contrasted by devastations and disillusionments. While the evolutionary spirit seems intent upon opening up a vast avenue for a new humanity through scientific, technological and progress in human relationship, an ominous sense of uncertainty and anxiety characterises our life – a situation that has brewed confusion in practically every aspect of our existence. Education is that which liberates – had been a cardinal doctrine in Indian prudence. Has that doctrine grown anachronistic? Is the sweeping spell of pragmatic, if not totally utilitarian, forces at work in the field of education necessarily the highest ideal because it is modern? It is time to have a deeper look at the very purpose of education – a question that spontaneously leads to the far more profound issue of the very purpose of life. Is there an ideal or a vision that can challenge the prevailing trends and offer us a way out of the present gloom? The talk will attempt a brief examination of these issues in the light of Sri Aurobindo’s vision of human destiny and education.